Reconstruction of Legal Norms Through Harmonization of Sexual Crime Laws - Febry Dwi Prehatiningsih; Edshafa Muharatulloh; Winda Rahmawati; Safira Wulandari; Tahegga Primananda Alfath (Universitas Negeri Semarang, 2023)
Harmonization and synchronization are required in the development of laws and regulations in order to strengthen the law and avoid overlapping regulations. Sexual crime legislation, there is the phrase